2018
DOI: 10.29252/archhygsci.7.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Accumulation and Human Health Risk of Trace Elements in the Vicinity of Industrial Estates, Central Iran

Abstract: Soil is a non-renewable dynamic natural resource that is essential to human life and serves as the most important sink for toxic ingredients like trace elements (1,2). There have been great concerns about the contamination of hazardous elements due to rapid industrialization and urbanization during the recent decades (3-6). Trace elements via urban soils can intake into the human body through three ways, ingestion, inhalation and dermal absorption, accumulate in fatty tissues, and subsequently affect the nervo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The spatial distribution (Fig. 2 other countries (e.g., Huang et al, 2007;Parizanganeh et al, 2010;Nekoeinia et al, 2016;Wu et al, 2018;Ravankhah et al, 2018).…”
Section: Spatial Distribution Of Hazardous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial distribution (Fig. 2 other countries (e.g., Huang et al, 2007;Parizanganeh et al, 2010;Nekoeinia et al, 2016;Wu et al, 2018;Ravankhah et al, 2018).…”
Section: Spatial Distribution Of Hazardous Materialsmentioning
confidence: 99%
“…Several previous studies related to petroleum compounds have reported sites polluted by oil refinery activities as well as land irrigation with untreated urban wastewater (Bayat et al, 2015;Bayat et al, 2016). Ravankhah et al (2018) studied the concentration and health risks of heavy metals in surface soil of Kashan city and reported that the soil is polluted by heavy metals due to industrial activities. Wu et al (2018)…”
Section: Introductionmentioning
confidence: 99%
“…With rapid urbanization and industrialization, urban soil pollution is becoming a serious problem worldwide and continues to attract increasing attention [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Soil management is a major component of agricultural food production, and soil serves as a sink for toxic substances, such as HMs [ 9 , 10 , 11 ]. Urban soils, including residential and park soils, which are the most common types of urban soils, expose local populations to HMs, and their contamination may have a direct effect on human health.…”
Section: Introductionmentioning
confidence: 99%